ANALISIS EFEKTIFITAS PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KABUPATEN LOMBOK BARAT NTB INDONESIA - Sasmitha, Baiq Tia (Master of Management, Mataram University, 2017)
PATEN is a form of the government response in responding to more complex demans and need of community. Nowdays, the sub-districts is required to be able to provide services for community proportionally based on the criteria and scope of sub-district level. Either in relation to licensing or non-licensing problems. On the other hand, the program face constraints that affect the ineffectiveness of the PATEN program. This research was focused on the anylisis of the effectiveness of PATEN implementation by the district government of West Lombok in the perspective of stakeholder. The data were collected through in-depth interview, documentation, and FGD. The research showed that the implementation of PATEN in West Lombok is not effective yet. This claim was based on the theory of the effectiveness proposed by Sharma in Tangkilisan (2005). Besides the finding in sub-districts showed that there were some factors causing the ineffectiveness of PATEN such as system, facilities, and human resources. Â Keywords:Â PATEN, Effectiveness, factors of effectiveness, solutions for the effectiveness